Exploring Traumatic Stress, Hope, Happiness, Resilience Among Palliative/Terminal Care & Neonate/Paediatric Care Nurses - Dushyant Kumawat; Mr. Samir Khan, (International Journal of Preventive Medicine and Health (IJPMH), 2025)
The present study was conducted to examine different psychological variables of female nurses working in Palliative and Neonatal care units across Government and Private hospitals in Delhi NCR, Karnataka, West Bengal, and Rajasthan states in India. The objective of the study to address significant gaps in the research by exploring the differences in experiences and psychological well-being amongst these healthcare professionals. The study compared the levels of traumatic stress, coping with grief, happiness, hope, and resilience between two groups of nurses, Palliative Care and Neonate Care. The results of the Independent-Samples Mann-Whitney U Test showed that there was no significant difference between the two groups in terms of their scores on any of the variables. Hope and resilience had a strong positive correlation with each other. However, most of the correlations were not statistically significant, indicating that there is no significant relationship between the dependent variables in this study. Overall, the results suggest that there is no significant difference between the perceptions of Palliative Care and Neonate Care nurses in terms of their coping with grief, hope, happiness, resilience, and traumatic stress, and there is no significant relationship between these variables. The findings of this study may provide crucial insights into the unique challenges that nurses working in specialized care settings face, including exposure to traumatic events and death and how their individual resources are allowing to deal with it. This knowledge can inform targeted interventions and support strategies to enhance their resilience and overall well-being. Ultimately, understanding the psychological well-being of these healthcare professionals is critical in ensuring they receive the necessary support and resources to cope with the demands of their job.